Racewalking on a treadmill alters gait characteristics without increasing risk of disqualification - Zhang, X.; Fong, D. T.; Zhang, C.; Song, S.; Wang, Y.; Sun, W.; Song, Q. (European Journal of Sport Science, 2023)
Purpose: Treadmill training is useful for racewalking training; however, it may affect gait characteristics and lead to non-legal techniques. The aim of this study was to determine the kinematic differences between treadmill and overground conditions during racewalking at different speeds. Methods: Twenty-two elite racewalkers participated in this study. They racewalked under treadmill and overground conditions at high and medium speeds. A 12-camera motion analysis system was used to record the racewalking trials. Results: Significant condition by speed interactions were detected in step frequency and pelvis rotation angle; step frequency decreased while pelvis rotation angle increased from overground to treadmill conditions at high speed. Compared to overground conditions, racewalkers decreased the ankle dorsiflexion angle at heel strike and increased hip flexion, shoulder hyperextension, and elbow flexion angles at heel strike and hip and shoulder extension angles at toe-off under treadmill conditions. Compared to medium speed, racewalkers decreased the contact time, hip flexion, and shoulder hyperextension at heel strike, and ankle plantarflexion and shoulder extension angles at toe-off, and increased flight time, step length, and elbow flexion angle at heel strike at high speed. Conclusion: Several kinematic differences during racewalking were detected between treadmill and overground conditions, with more differences detected at high speed, indicating that treadmill racewalking, especially at high speed, has different gait characteristics. However, no differences were detected in flight time and knee angle under treadmill conditions compared to overground conditions, indicating that racewalking on a treadmill does not increase the risk of disqualification.